Current strategies for quantification of estrogens in clinical research. Issue 192 (September 2019) - Denver, Nina; Khan, Shazia; Homer, Natalie Z.M.; MacLean, Margaret R.; Andrew, Ruth
Highlights: Profiling estrogens and their metabolites by mass spectrometry (MS) offers insights into health and disease. Low limits of quantification can be achieved by MS approaches, interfaced with GC or LC. Improvements in recovery, ion suppression and detection are discussed. Advances in current technologies for future method development strategies are proposed. Abstract: Estrogens and their bioactive metabolites play key roles in regulating diverse processes in health and disease. In particular, estrogens and estrogenic metabolites have shown both protective and non-protective effects on disease pathobiology, implicating the importance of this steroid pathway in disease diagnostics and monitoring. All estrogens circulate in a wide range of concentrations, which in some patient cohorts can be extremely low. However, elevated levels of estradiol are reported in disease. For example, in pulmonary arterial hypertension (PAH) elevated levels have been reported in men and postmenopausal women. Conventional immunoassay techniques have come under scrutiny, with their selectivity, accuracy and precision coming into question. Analytical methodologies such as gas and liquid chromatography coupled to single and tandem mass spectrometric approaches (GC–MS, GC–MS/MS, LC–MS and LC–MS/MS) have been developed to quantify endogenous estrogens and in some cases their bioactive metabolites in biological fluids such as urine, serum, plasma and saliva. Liquid-liquid or solid-phase extraction approaches are favoured with derivatization remaining a necessity for detection in lower volumes of sample. The limits of quantitation of individual assays vary but are commonly in the range of 0.5–5 pg/mL for estrone and estradiol, with limits for their bioactive metabolites being higher. This review provides an overview of current approaches for measurement of unconjugated estrogens in biological matrices by MS, highlighting the advances in this field and the challenges remaining for routine use in the clinical and research environment.